13-7x+3x=-6-5x+3

Simple and best practice solution for 13-7x+3x=-6-5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-7x+3x=-6-5x+3 equation:


Simplifying
13 + -7x + 3x = -6 + -5x + 3

Combine like terms: -7x + 3x = -4x
13 + -4x = -6 + -5x + 3

Reorder the terms:
13 + -4x = -6 + 3 + -5x

Combine like terms: -6 + 3 = -3
13 + -4x = -3 + -5x

Solving
13 + -4x = -3 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
13 + -4x + 5x = -3 + -5x + 5x

Combine like terms: -4x + 5x = 1x
13 + 1x = -3 + -5x + 5x

Combine like terms: -5x + 5x = 0
13 + 1x = -3 + 0
13 + 1x = -3

Add '-13' to each side of the equation.
13 + -13 + 1x = -3 + -13

Combine like terms: 13 + -13 = 0
0 + 1x = -3 + -13
1x = -3 + -13

Combine like terms: -3 + -13 = -16
1x = -16

Divide each side by '1'.
x = -16

Simplifying
x = -16

See similar equations:

| 13x+2y=407 | | 9a-5*a=7 | | 132=c-(249) | | 132=(-249) | | 11x=3600+6x | | 2x+10y=34 | | (x)(x)-11x-80=0 | | 3x+7=x+41 | | 24x+10x+1=0 | | Lnx(Lnx-4)=0 | | X-.35x=50000 | | 4p^2-8p+578=0 | | 3x+5+7x-10=90 | | x^3-1.413*x^2+0.013=0 | | 2(5y+6)=82 | | log[7](4)-log[7](3x)= | | 0=4b^2-76b+16 | | 4x+6=5-3x | | 0=4b^2-200b+16 | | x^2+5mx+16=0 | | 0=4b^2-96b+16 | | x+7/6-x/3=-2 | | 0=12t^2-42t+30 | | 3x-2+2y+1+x-w+1+3-4w=22 | | 4t+7=9t-13 | | 25x^2-160x+220=0 | | 0=b^2-24b+4 | | 2/x+1/x-1=2 | | 0=b^2-24h+4 | | b(2x+b)=0 | | 60*5=678 | | 25x^2-16x+220=0 |

Equations solver categories